Ecology, anatomy and redescription of Laternea pusilla - Sáenz, J. A. (1976)
Laternea pusilla, found on rotting logs in Costa Rica (Central America) is redescribed. The receptacle is formed by 2, 3, or 4 arms instead of just 2 as originally reported. Comparative ecological observations of the species during several months, in its natural habitat and at different altitudes and environments are presented.Anatomical studies show that the receptacle of L. pusilla originates from primordial tissue above the rhizomorph. Initially the recentacle forms a chambered unit which branches into 2, 3, or 4 arms, similarly chambered. The branches finally encompass the gleba, which is swept up and left suspended underneath the arch of the receptacle arms. As the fruiting body develops, the outer chambers of the arms are disrupted and form the crests of the mature body, while the upper inner chambers give rise to the trabecular structure that holds the lantern and the suspended gleba.Laternea is shown to be the valid name for the genus rather than Colonnaria Raf., which is either a synonym of Clathrus or a third genus. Colonnaria pereximia L. D. Gómez, on the basis of the variability of Laternea pusilla as to the number of arms of the receptacle, is considered synonymous with the latter.